Isolation and characterization of nonsense mutations in gene 10 of bacteriophage phi 6. - Johnson, M D (1994)
Nonsense mutants of bacteriophage phi 6 were isolated by a procedure that involved directed mutagenesis of a cDNA copy of genomic segment M, transcription of this segment, in vitro packaging into procapsids, and transfection of spheroplasts to form viable mutant phage. Recombinant phi 6 viruses that contained amber mutations in two open reading frames, ORF 10 and ORF D, of genomic segment M were isolated. We show that phi 6 protein P10 is the gene product of ORF 10. Further characterization of the phi 6 ORF 10(Am) mutant revealed that phi 6 membrane-associated protein P10 is not required to make enveloped phage particles in infected cells. Enveloped phage particles isolated from a phi 6 ORF 10(Am) infection contained extremely low levels of phi 6 membrane-associated proteins P6 and P3. The low abundance is due to the very low level of P6 synthesis in phi 6 ORF 10(Am)-infected cells. The results suggest that P10 might play a role in regulating the translation of gene 6. Protein P10 was found to be required for host lysis.